I have attached this which I have having trouble proving.
Can anyone point me in the right direction on how to start this?
$\displaystyle \frac{1}{1+t^b} = \frac{1}{1 - (-t^b)} = 1 - t^b + t^{2b} - t^{3b} + ...$
$\displaystyle \frac{t^{a-1}}{1+t^b} = t^{a-1} - t^{a+b-1} + t^{a+2b-1} - t^{a+3b-1} + ...$
$\displaystyle \int_0^1 \frac{t^{a-1}}{1+t^b} dt = $
$\displaystyle \left[\frac{t^a}{a} - \frac{t^{a+b}}{a+b} + \frac{t^{a+2b}}{a+2b} - \frac{t^{a+3b}}{a+3b} + ... \right]_0^1 = \frac{1}{a} - \frac{1}{a+b} + \frac{1}{a+2b} - \frac{1}{a+3b} + ...$